Immunosensing for Early Detection of Rheumatoid Arthritis Biomarkers: Anti-Cyclic Citrullinated Peptide Antibodies Based on Tilted-Fiber Bragg Grating Biosensor - Hsin-Yi Wen; Chia-Chin Chiang; Rou-Yu Chen; Wei-Zhi Ni; Yu-Qiao Weng; Yao-Tsung Yeh; Hsiang-Cheng Hsu (Bioengineering, 2023)
Rheumatoid arthritis (RA) is regarded as a chronic, immune-mediated disease that leads to the damage of various types of immune cells and signal networks, followed by inappropriate tissue repair and organ damage. RA is primarily manifested in the joints, but also manifests in the lungs and the vascular system. This study developed a method for the in vitro detection of RA through cyclic citrullinated peptide (CCP) antibodies and antigens. The diameter of a tilted-fiber Bragg grating (TFBG) biosensor was etched to 50 μm and then bonded with CCP antigens and antibodies. The small variations in the external refractive index and the optical fiber cladding were measured. The results indicated that the self-assembled layer of the TFBG biosensor was capable of detecting pre- and post-immune CCP antigen and CCP peptide concentrations within four minutes. A minimum CCP concentration of 1 ng/mL was detected with this method. This method is characterized by the sensor’s specificity, ability to detect CCP reactions, user-friendliness, and lack of requirement for professional analytical skills, as the detections are carried out by simply loading and releasing the test samples onto the platform. This study provides a novel approach to medical immunosensing analysis and detection. Although the results for the detection of different concentrations of CCP antigen are not yet clear, it was possible to prove the concept that the biosensor is feasible even if the measurement is not easy and accurate at this stage. Further study and improvement are required.